Phylogenetic relationships of Fusarium poae based on EF-1 alpha and mtSSU sequences - Stenglein, Sebastián (2010)
A molecular phylogenetic analysis ofFusarium poaeisolates from South America (Argentina) and Europe (mainly England, Germany, Italy) was performed using 98F. poae, fourFusarium culmorum, twoFusarium sporotrichioidesand oneFusarium langsethiaeisolates. Phylogenetic analyses were performed using nuclear (translation elongation factor 1-alpha,EF-1α) and mitochondrial (mitochondrial small subunit rDNA,mtSSU) sequences. Partitioned (each dataset separately) and combined (EF-1α+mtSSU) analyses did not reveal any clear correlations from the inferred branching topology, between the distribution of observed haplotypes and the geographic origin and/or host species. Results from the present study confirmed that isolates fromF. poaeform a monophyletic group, and the low variability within isolates from a broad geographic range suggests a common lineage history. AmongF. poaeisolates from Argentina, however, some were found to possess an insert withinmtSSUwith structural similarities to group IC2 introns.F. poaeisolates differing by the presence/absence of amtSSUinsertion were characterized further by analysis of a portion of theTri5gene, but this sequence was unable to reveal variability. The presence of this insert only within isolates from Argentina suggests that evolutionary events (insertions/deletions) are probably taking place within the ArgentinianF. poaeisolates, and that the acquisition of this insert occurred after geographic isolation of the Argentinian and European populations.